Antioxidant Activity and Total Phenolic Content of Various Extracts from Mimosa hamata Willd., Mimosaceae - Renu Singh; Satish C. Jain; Y. T. Jasrai (International Journal of Phytomedicine, 2012)
Jinjani (Mimosa hamata Willd., Mimosaceae) is widely distributed in India and Pakistan, which contains several interesting bioactive constituents and possesses health promoting properties. In this study, the antioxidant activity with the total phenolic content of different successive extracts (pet. ether, chloroform, n-butanol and water) from leaves, stem, root and seeds of M. hamata were assessed in an effort to compare and validate the antioxidant potential of the particular part of the plant. The antioxidant activity was determined by 2, 2- Diphenyl-1-picrylhydrazyl (DPPH) assay and total phenolic content was estimated by using Folin-Ciocalteu’s reagent. All tested extracts possessed appreciable antioxidant potential but n-butanol extract of roots was significantly higher in total phenolic content (73.16±0.19 mg GAE/g extract) and in antioxidant assay (IC50 = 5µg/ml). It is also noteworthy that in nbutanol extract of roots higher yield (85.60%) was also observed. This study validates the antioxidant potential of the roots in M. hamata and the positive relationship between total phenolic content and antioxidant activity.